The Effect of β2-Adrenoceptor Agonists on Leucocyte-Endothelial Adhesion in a Rodent Model of Laparotomy and Endotoxemia - Bangash, Mansoor Nawaz; Abbott, Tom E. F.; Patel, Nimesh S. A.; Hinds, Charles Johnston; Thiemermann, Christoph; Pearse, Rupert Mark (Frontiers in Immunology, 2020)
Abstract Background The β2-adrenoceptor agonist dopexamine may possess anti-inflammatory actions which could reduce organ injury during endotoxaemia and laparotomy. Related effects on leucocyte-endothelial adhesion remain unclear. Methods Thirty anaesthetised Wistar rats underwent laparotomy followed by induction of endotoxaemia with lipopolysaccharide and peptidoglycan (n=24) or sham (n=6). Animals received dopexamine at 0.5 or 1 µg kg-1 min-1 (D0.5 and D1), salbutamol at 0.1 µg kg-1 min-1, or saline vehicle (Sham and Control) for five hours. Intravital microscopy was performed in the ileum of the small intestine to assess leucocyteendothelial adhesion, arteriolar diameter, and functional capillary density. Global haemodynamics and biochemical indices of renal and hepatic function were also measured. Results Endotoxaemia was associated with an increase in adherent leucocytes in post-capillary venules, intestinal arteriolar vasoconstriction as well reduced arterial pressure and relative cardiac index, but functional capillary density in the muscularis was not significantly altered. Dopexamine and salbutamol administration were associated with reduced leucocyte-endothelial adhesion in post-capillary venules compared to control animals. Arteriolar diameter, arterial pressure and relative cardiac index all remained similar between treated animals and controls. Functional capillary density was similar for all groups. Control group creatinine was significantly increased compared to sham and higher dose dopexamine. Conclusions In a rodent model of laparotomy and endotoxaemia, β2-agonists were associated with reduced leucocyte-endothelial adhesion in post-capillary venules. This effect may explain some of the anti-inflammatory actions of these agents.